2021
DOI: 10.1101/2021.03.26.21254421
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimating COVID-19 cases and deaths prevented by non-pharmaceutical interventions, and the impact of individual actions: a retrospective model-based analysis

Abstract: Simulation models from the early COVID-19 pandemic highlighted the urgency of applying non-pharmacetical interventions (NPIs), but had limited empirical data to use. Here we use data from 2020-2021 to retrospectively model the impact of NPIs. Our model represents age groups and census division in Ontario, Canada, and is parameterised with epidemiological, testing, demographic, travel, and mobility data. The model captures how individuals adopt NPIs in response to reported cases. The model predicts that school/… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Most mathematical modelling of infectious disease occurs at the population scale and throughout the COVID-19 pandemic there have been many such studies (cf. Tang et al (2020); Moyles et al (2021); Yuan et al (2022a); Fair et al (2022); Childs et al (2022); Vignals et al (2021); Betti et al (2021); Dick et al (2021); Moore et al (2021); Moss et al (2020); Smirnova et al (2021); Wells et al (2021); Li et al (2020); Yuan et al (2022b); Hogan et al (2021)). While the impacts of vaccine efficacy and waning are important at these scales, the actual process of immune development occurs within-host.…”
Section: Introductionmentioning
confidence: 99%
“…Most mathematical modelling of infectious disease occurs at the population scale and throughout the COVID-19 pandemic there have been many such studies (cf. Tang et al (2020); Moyles et al (2021); Yuan et al (2022a); Fair et al (2022); Childs et al (2022); Vignals et al (2021); Betti et al (2021); Dick et al (2021); Moore et al (2021); Moss et al (2020); Smirnova et al (2021); Wells et al (2021); Li et al (2020); Yuan et al (2022b); Hogan et al (2021)). While the impacts of vaccine efficacy and waning are important at these scales, the actual process of immune development occurs within-host.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown, for instance, the necessity of keeping NPIs in place during the vaccine rollout in 2021, a year after the start of the pandemic (1,2). The literature on the usefulness of NPIs and their effects on the transmission dynamics of COVID-19 is vast (3)(4)(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism may be relevant to severe coronavirus 2 (SARS-CoV-2) transmission, where scalable NPIs have been highly successful in preventing cases and deaths [17, 18]. Here we develop a stochastic model of SARS-CoV-2 transmission in a population.…”
Section: Introductionmentioning
confidence: 99%